Incorporation of Silica Nanoparticles in Dental Stone Type IV: Effects on Setting Time - Fahimi, Mahsa; Torab, Ali; Mahboub, Farhang; Rezaei, Yashar; Jafarabadi, Sara Haji; Radesh, Parsa; Dizaj, Solmaz Maleki (Current Nanomedicine, 2024)
<span class=
Keywords: gypsum